Research in social movements, conflicts and change. Vol. 30 - Coy, Patrick G. (Bingley, UK : Emerald, 2010)
Research in Social Movements, Conflicts and Change seeks to encourage dialogue and cross-fertilization across a number of related but too disconnected research literatures: social movements, conflict resolution, and social and political change. This volume showcases deeply empirical and often multi-method research by senior and junior scholars alike. Divided into three sections, the first section casts a spotlight on the institution that the RSMCC series exists within and primarily serves: higher education. Papers in the middle section are linked by their investigation of the dynamics of political protest. The volume concludes with three papers linked by their various connections to the theoretical framework of frame analysis in social movements research. Topics discussed include: framing illegal immigration at the U.S.-Mexican Border; movement publications as data; social networks and social protest; and the ethics of social movement research in a post-9/11 political climate. Comparative case analysis and qualitative studies push into new theoretical territories in this illuminating and important research which helps define and advance the multiple fields reflected in the series title.
Introduction / Patrick G. Coy -- Spotlight on the academy -- "It's part of my being": demand-making and discursive protests by feminist sociologists inside academia / Heather Laube -- Risks and ethics of social movement research in a changing political climate / Kathleen M. Blee and Tim Vining -- The politics of public protest -- The impacts of repression: the effect of police presence and action on subsequent protest rates / Jennifer Earl and Sarah A. Soule -- On social networks and social protest: understanding the role of organizational and persoanl ties in large-scale protest events / Dana R. Fisher -- Legal dissent: Constitutional proposals for "Cambio" in Cuba / Ana Cristina Maldonado -- Bridging continentious and electoral politics: Moveon and the digital revolution / Victoria Carty -- Extending framing theory in multiple directions -- Framing illegal immigration at the U.S.-Mexican border: anti-illegal immigration groups and the importance of place in framing / April Lee Dove -- The dilemma of differential mobilization: framing strategies and shaping engagement in the occupation of Alcatraz / Christopher Wetzel -- Movement publications as data: an assessment of an underutilized resource / Andrew W. Martin.
Includes bibliographical references.
Description based on print version record.
Keywords: Social movements; Social conflict; Social psychology; Social issues & processes; Social Science -- Sociology -- General